University Students’ Perceptions and Practices of AI-Assisted Writing Tools in Academic Writing - Moh. Taufik; Yuni Putri Utami; Faizatul Hayati; Achmad Faqih; Awati Fane; Marisa Linia (PT. Intelek Cendikiawan Nusantara, 2025)
The rapid development of Artificial Intelligence (AI) has significantly transformed academic writing practices in higher education, particularly in EFL contexts. This study aims to explore university students’ perceptions and practices of using AI-assisted writing tools in academic writing. A descriptive qualitative design supported by quantitative data was employed. The participants were undergraduate students enrolled in academic writing-related courses who had experience using AI-assisted writing tools. Data were collected through questionnaires, semi-structured interviews, and document analysis of students’ academic writing. Questionnaire data were analyzed using descriptive statistics, while interview and document data were analyzed thematically. The findings indicate that students hold positive perceptions toward AI-assisted writing tools, particularly in terms of perceived usefulness, ease of use, and increased writing confidence. In practice, students most frequently utilized AI tools during the revising and editing stages, mainly to improve grammatical accuracy, vocabulary choice, and sentence clarity. Furthermore, the study reveals a notable level of ethical awareness, as students tended to limit AI use to language-level support rather than idea generation. The study concludes that AI-assisted writing tools have considerable potential to support academic writing development and self-regulated learning when integrated responsibly. Pedagogical implications highlight the importance of instructional guidance in fostering ethical and effective AI use in academic writing instruction.